Instructional leadership as a predictor of resilience and well-being in STEM learning: a systematic review - Dogaru, Mariana; Negreanu, Mirela Cristina; Pisică, Olivia; Pîrvu, Alina Florentina (Frontiers in Education, 2026)
BackgroundInstructional leadership (IL) is critical for fostering resilience and well-being in STEM education, yet its impact remains underexplored. This systematic review synthesizes evidence on how IL predicts resilience and well-being in STEM learning.MethodsFollowing PRISMA guidelines, we analyzed 80 peer-reviewed studies (2014–2024) from Clarivate, Scopus, Google Scholar, and ERIH Plus, using keywords like „instructional leadership” and „STEM education.”ResultsIL indirectly enhances resilience through strong teacher-student relationships and supports well-being by boosting motivation in STEM. Success in STEM subjects fosters school resilience, while cognitive conflict in STEM learning contributes to adaptive strategies.ConclusionIL is a key predictor of STEM learning outcomes, with implications for teacher training and inclusive STEM curricula. Future research should explore contextual factors mediating these relationships.